1984
DOI: 10.1002/1097-0142(19841101)54:9<1854::aid-cncr2820540915>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for major salivary gland carcinoma. A case-comparison study

Abstract: The authors conducted a case‐comparison chart‐review study on 498 patients with histologically confirmed salivary gland carcinoma and 487 randomly selected patients registered at The University of Texas M. D. Anderson Hospital and Tumor Institute at Houston from 1960 through 1981. The study was undertaken to identify potential risk factors for salivary gland carcinoma. Univariate analysis of the data indicated a relationship with prior radiation therapy (odds ratio estimate of 6.17 with 95% confidence limits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 13 publications
7
55
2
Order By: Relevance
“…20,21 The cancer induction time is relatively long for solid tumours; for exposures during childhood and adolescence, the induction period is 10-35 years. 22 There are a few epidemiological studies on a possible relationship between dental radiography and salivary gland cancer.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 The cancer induction time is relatively long for solid tumours; for exposures during childhood and adolescence, the induction period is 10-35 years. 22 There are a few epidemiological studies on a possible relationship between dental radiography and salivary gland cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation to the head and neck is one potential cause. A number of studies found an association between external radiation therapy to the head and neck and subsequent development of salivary gland malignancies, especially in children (Maxon et al, 1981;Modan et al, 1974;Palmer et al, 1980;Spitz et al, 1984). A similar association was observed in survivors of the atomic bombing of Japan (Belsky et al, 1975).…”
mentioning
confidence: 86%
“…Contrasting from the more common mucosal head and neck cancers, which, in general, are ascribed to excessive tobacco, alcohol use, and more recently to viral infection (HPV), specific carcinogenic factors for malignant salivary gland growths have not been as clearly identified. Exposure to ionizing radiation [2][3][4][5][6][7][8] has been implicated as a cause of salivary gland cancer as well as certain occupational exposures, such as, rubber products manufacturing, asbestos mining, plumbing, and some types of woodworking [9,10].…”
Section: Introductionmentioning
confidence: 99%